COMPARATIVE MORPHOLOGICAL AND MICROCIRCULATORY CHANGES IN THE LYMPHOID STRUCTURES OF THE SPLEEN OF WHITE RATS DUE TO MAGNESION DEFICIENCY (World Bulletin of Public Health, 2025)
In the article, comparative morphological and microcirculatory changes in the lymphoid structures of the spleen of white rats caused by magnesium deficiency were studied. In the study, morphometric parameters, cellular composition, and microcirculatory changes in the lymphoid tissue of the spleen in magnesium deficiency were analyzed based on an experimental model. The results showed that in alimentary magnesium deficiency, a decrease in the morphometric parameters of lymphoid tissue and the number of lymphoid cells in this organ, an increase in the thickness of the vascular wall, and a decrease in the internal diameter were revealed. The study showed that magnesium deficiency significantly affects the immunobiological function of the spleen and causes degenerative and vascular changes in lymphoid structures. The obtained results serve for a deeper understanding of the morphofunctional processes occurring in the immune system during magnesium deficiency and in the future builds.
Keywords: magnesium failure; spleen; limfoid structures; white rats